Slides to Philosophy 167: Class 13 -- Newton's De Motu Corporum in Gyrum (i.e. Version 1) -- Part 11. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 13, Part 11.